Cytotoxicity and anti-inflammatory activities of Gallesia integrifolia (Phytolaccaceae) fruit essential oil - Bortolucci, Wanessa C. (2018)
The chemical composition of Gallesia integrifolia fruits essential oil was obtained by hydrodistillation using a modified Clevenger apparatus was investigated by gas chromatography coupled to mass spectrometry (GC/MS). In addition, the cytotoxicity activity against human tumor cell lines MCF-7 (breast adenocarcinoma), NCI-H460 (large cell lung carcinoma), HeLa (cervical carcinoma), and HepG2 (hepatocellular carcinoma), and non-tumor PLP2 (porcine liver primary cells) as well as the anti-inflammatory action was proposal. The compounds were predominantly organosulfates (2,8-dithianonane, dimethyl trisulfide, and lenthionine). Anti-inflammatory activity that provides 50% inhibition of nitric oxide production (55 µg/mL) of essential oil of the fruits. It also presents cytotoxic activity against MCF-7 (GI50 = 66 µg/mL), NCI-H-460 (GI50 = 147 µg/mL), HeLa (GI50 = 182 µg/mL) and HepG2 (GI50 = 240 µg/mL). The essential oil is more active in tumor cells than in non-tumor cells and the GI50 values for essential oil reported in our work support future studies.